Finnish Paraphrase Corpus - Kanerva Jenna; Ginter Filip; Chang Li-Hsin; Rastas Iiro; Skantsi Valtteri; Kilpeläinen Jemina; Kupari Hanna-Mari; Saarni Jenna; Sevón Maija; Tarkka Otto (Sweden, 2025)
In this paper, we introduce the firstfully manually annotated paraphrase cor-pus for Finnish containing 53,572 para-phrase pairs harvested from alternative subtitles and news headings. Out of all paraphrase pairs in our corpus 98% are manually classified to be paraphrases at least in their given context, if not in all contexts. Additionally, we establish a manual candidate selection method and demonstrate its feasibility in high quality paraphrase selection in terms of both costand quality.
Proceedings of the 23rd Nordic Conference on Computational Linguistics (NoDaLiDa 2021)